The Influence of Global Risks on the Composite Index - Andriyani, Rodhiya; Pimada, Laila (Journal of Development Economic and Social Studies, 2025)
This research investigates the influence of Geopolitical Risk (GPR), Economic Policy Uncertainty (EPU), the Volatility Index (VIX), and Brent oil prices on the Jakarta Composite Index (JCI) in Indonesia. By incorporating all major global uncertainty factors into a single model, this study bridges a gap in the existing literature, which often analyzes these variables separately. The research employs the Autoregressive Distributed Lag (ARDL) model using monthly data from 2018 to 2024 to capture both short-run and long-run dynamics between the variables. The empirical results reveal that Brent oil prices exhibit a significant positive relationship with the JCI, implying that higher oil prices may enhance market sentiment and investment value in resource-dependent economies. Conversely, the VIX demonstrates a strong and significant negative relationship with the JCI, suggesting that rising global market volatility suppresses investor confidence and capital inflows. However, neither geopolitical risk nor economic policy uncertainty shows a statistically significant impact on the JCI. These findings provide valuable insights for policymakers and investors, emphasizing the relative resilience of the Indonesian stock market amid global financial and political turbulence.